The Effect of Using Gadgets on The Level of Learning and Spirituality of Students During The Covid-19 Pandemic - Nur Zaytun Hasanah; Istiqomah Istiqomah; Kurniawan Dwi Saputra (Edunesia: Jurnal Ilmiah Pendidikan, 2022)
Talking about education is certainly closely related to the generation of students. If we look at the current state of education, especially the quality that exists within students, it is very concerning. Cellphones that should be used for learning in schools are now only limited to playing games. Not a few students want to read textbooks, because they are busy reading chats from their girlfriends. Not even a few studens go to the mosque to perform Dhuha prayers and Fardhu prayers because they are busy tik-tokan. Generations of students are starting to spend a lot of time in front of gadgets. The generation that Allah says in the Qur’an as the Khoiru Ummah, is now a rare thing to see.The purpose of this study was to interpret the influence of gadgets on the level of learning and spirituality of students during the covid-19 pandemi. This research is a type of qualitative research with a qualitative descriptive research approach. Data collection techniques used are observation methods, documentation methods and interview methods. The data analysis technique used is Milles, Huberman and Saldana with the stages of data collection, data condensation, data presentation and drawing conclusions. The results showed that the influence of gadgets on the level of student learning, greatly decreased. Likewise, the level of spirituality of students during the Covid-19 pandemi, is very low. This is evidenced by the teachers who teach students at Madrasah every day, as well as student learning outcomes when doing daily tests and when doing assignments both at school and at home.